COMPARISON OF HEMODYNAMIC EFFECT CAUSED BY INTRATHECAL LOW DOSE ADMINISTRATION OF 0.5% AGAINST 0.75% HYPERBARIC BUPIVACAINE IN PATIENTS UNDERGOING LOWER LIMB SURGERY UNDER UNILATERAL SPINAL ANAESTHESIA - Khan, Maliha Khalid; Amran Hafiz,; Faheem Feroze,; Anjum Atique Tahir,; Saeed Farooq,; Muhammad Shaheer Bin Faheem, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Spinal anaesthesia has its unique place in modern anaesthetic practice. In past, most of the surgeries, irrespective of the site of surgery, were performed in general anaesthesia but now in the modern anaesthetic field, spinal anaesthesia has markedly replaced general anaesthesia, specifically in obstetrics, lower limbs, and abdominal surgeries. Methods: A total of 100 patients fit to undergo lower limb surgery between the ages of 20 to 70 years were included in the study. 50 patients were in 0.5% hyperbaric bupivacaine (Group A) while 50 patients were in the 0.75% hyperbaric bupivacaine group (Group B). Patients with a history of allergies to local anaesthetics, ischemic heart disease and contraindications to spinal anaesthesia were excluded. At the end of the injection, the patient was immediately laid down and tilted to 30 degrees lateral on the operative side for unilateral anaesthesia. Mean arterial pressure at baseline, 15, 30, 45 and 60 minutes was recorded by trainee anaesthesia. A baseline was taken of mean arterial pressure measured 15 minutes before induction of spinal anaesthesia in a lying position. Results: The mean baseline arterial pressure of patients in group A was 88.72±1.71 mmHg and in group B was 88.94±1.95 mmHg. Mean arterial pressure MAP at 15, 30, 45 and 60 minutes in both groups was as follows; 86.22±2.55 vs 81.78±1.52 mmHg, 83.72±3.36 vs 75.84±1.34 mmHg, 80.02±3.40 vs 70.90±0.97 mmHg and 77.14±4.24 vs 66.06±1.62 mmHg respectively (p-value <0.05). Conclusion: This study concluded that the hemodynamic parameters in terms of mean arterial pressure remained more stable by deviating less from the baseline value with the use of a low dose of 0.5% hyperbaric bupivacaine instead of 0.75% hyperbaric bupivacaine in patients undergoing lower limb surgery under unilateral spinal anaesthesia.